Pengaruh Self Motivation dan Lingkungan Kerja terhadap Retensi Perawat Siloam Hospital Tb Simatupang - Benedikta Rina Pratiwi; Supriyantoro Supriyantoro; Hasyim Hasyim (Jurnal Manajemen Kesehatan Indonesia, 2021)
The nurse shortage crisis is caused by the high turnover of nurses related to management practices that were not running optimally. Anticipatory efforts are critical to increase nurse retention by increasing self-motivation and work environment to increase job satisfaction on nurses as an impact. This study aimed to provide empirical evidence of the effect of self-motivation and work environment on nurse retention with job satisfaction as an intervening variable. This research used quantitative research with survey methods using questionnaires. The unit of analysis was a group of nurses PK 1 as many as 61 people. Data analysis used path analysis with multiple linear regression as the data analysis technique. Results showed that self-motivation and work environment had a significant effect on nurse retention with job satisfaction as an intervening variable. The variables of self-motivation and work environment each had a significant effect on job satisfaction. The variables of self-motivation, work environment, and job satisfaction each had a significant effect on nurse retention. The findings indicate that employees are dissatisfied with the work environment, both physical and non-physical, as well as the compensation and rewards provided by the company. We suggest to the hospital to give awards in the form of bonuses or incentives to nurses in accordance with work assessments. We also suggest for further research to examine more deeply about the four variables in this study with other research subjects to compare with the results of the research